Career Wellbeing for Workers with Physical Disabilities: A Phenomenology Study - Dhini Rama Dhania (Journal of Educational, Health and Community Psychology, 2023)
Career well-being is essential for activating adaptive readiness when facing challenges. It serves as a valuable tool in career development interventions, particularly in assisting workers in overcoming work-related difficulties, especially for those with disabilities. Therefore, the objective of this study was to explore the career well-being of disabled workers. This study employs a phenomenological qualitative approach. The sampling technique used was purposive, targeting workers with physical disabilities who have been employed by a company for at least 1 year and have completed at least junior high school education. Data collection involved semi-structured interviews conducted with 6 employees with physical disabilities. The findings reveal the following: (1) The career well-being of workers with physical disabilities can be categorized into three themes. Firstly, there's a positive emotional impact on their career situations, as they express gratitude and happiness for being accepted at work, fulfilling their aspirations. Secondly, these individuals find meaning in their career situations, deriving significance for themselves, their families, and their companies due to the trust and responsibility vested in them. Thirdly, the status of career networks and social support plays a pivotal role, as evident through their involvement with the FKDK community and within the company. (2) Additionally, the factors influencing the career well-being of workers with physical disabilities stem from both internal and external sources. Internally, self-motivation plays a vital role, whereas externally, support from parents, spouses, and the company contributes significantly. This study's findings provide a substantial contribution to the comprehension of career well-being among workers with physical disabilities.